Voluntary Counseling and Testing (VCT) Application for HIVDS Counselors - hendra, syaiful; Ngemba, Hajra Rasmita; Dodu , Albertch Yordanus Erwin; Nur, Rosmala; P. Dominggo, Nenita; Rantung, Vivi; Lintine, Gabriella Bamba Ratih; Tanaem, Penidas Fiodinggo; Putra Ramadhan, Adjie (Tadulako Science and Technology Journal, 2020)
program (unreached population) such as clients who visit independent practice health services, clients who seek treatment themselves with alternative medicine or buy drugs at pharmacies that are not in accordance. This study aims to design a model that can help the government in HIV case through counsellors aiming to reduce the spread of the infectious diseases. Methods: The type of research conducted is applied research. This research designed and built a model to help counsellors and clients during the treatment period. The study was conducted in Palu City with a number of samples scattered in 8 Voluntary Counselling and Testing (VCT) clinics . Results: The model developed resulted in an Electronic HIV Control and Counselling Care (E-HC3) application that can help counsellors dealing with large numbers of clients and are private. Applications built have three levels, in which the first level is as a super admin (government), the second level is an admin (counsellor) and level three is the client . Conclusion This app is very helpful for counseling HIV-AIDS counselors and clients based on application testing. It is known that the E-VCT application counselor's assessment of the total percentage value of the five variables tested was 80.10% with a very good acceptance rate from the user of the E-VCT Application.